THE NEW ORDER OF GENDER STUDIES IN THE QURANIC WORLDVIEW - Pambayun, Ellys Lestari (Moderation | Journal of Islamic Studies Review, 2021)
Abstract: Worldview is a framework of thinking or fundamental beliefs about our vision of the world and a vision of our shadow or expression in the future. The term worldview is also used in Islam to explore the reality of the world through a set of Qur'an-based and hadith-based knowledge such as al-mabda', al-nazariyat, al-tawassur al-Islamiyah, and so on. The worldview device as an important element in seeing human reality refers to the three pillars of philosophy, namely epistemology, ontology, and axiology. Epistemilogy in looking at gender metamorphoses from just a definition, a concept to a study or theory. In Islam the epistemological concept is used to look at gender in two approaches: the epistemology of the bayani (a more rational worldview based on the Quranic text in viewing gender bias) and the burhani epistemology (worldview of gender in rabbaniyah, thabat, syumul, waqi'iyah, ijabbiyah, tawazun, and tawhid). In gender ontology it is discussed in its essence or "being". The perspective of Western thinkers (liberal feminism, radical feminism, postmodern feminism, existensial feminism, psychoanalysis feminis, Asia feminism, etc) and Modern Islam (Islamic femins) views the nature of gender as social construction which say that the gender world constructed by social and culture consensus not fitrah, whereas Islamic thinkers see that the Qur'an forms gender equality in essence to undermine the notion of radical differences and gender hierarchies related to the origin of human creation. As for axiology, gender studies have value to the extent that studies have benefits or benefits to others. Finally, gender studies in the view of the Qur'an are "to see" men and women not only inseparable, but also the same as Allah says specially ain Surat Al-Nisa 'verse 1 and the othe verses